"It's about making adolescents in charge of their health": policy-makers' perspectives on optimizing the health care transition among adolescents living with HIV in Kenya. Issue 9 (2nd September 2022) - Shulock, Katherine; Beima-Sofie, Kristin; Apriyanto, Haris; Njuguna, Irene; Mburu, Caren; Mugo, Cyrus; Itindi, Janet; Onyango, Alvin; Wamalwa, Dalton; John-Stewart, Grace; O'Malley, Gabrielle
ABSTRACT : The health care transition (HCT) from pediatric to adult care is a potential contributor to poor clinical outcomes among adolescents living with HIV (ALHIV). In sub-Saharan Africa (SSA), there is limited information on effective tools and processes to prepare and support ALHIV through this transition. This study elicited perspectives of policy-makers regarding barriers and facilitators to successful HCT among ALHIV in Kenya. Twenty in-depth interviews (IDIs) were conducted with policy-makers using a semi-structured guide. Using the socio-ecological model (SEM) as an organizing framework, directed content and thematic network analyses methods were used to characterize themes related to key influences on HCT processes and to describe actionable recommendations for improved tools and resources. Policy-makers identified multilevel support, including the development of a triadic relationship between the caregiver, healthcare worker (HCW) and adolescent, as an essential strategy for improved HCT success. Across the SEM, policy-makers described the importance of actively engaging adolescents in their care to promote increased ownership and autonomy over health decisions. At the structural level, the need for more comprehensive HCT guidelines and improved HCW training was highlighted. Expanded HCT tools and guidelines, that emphasize supportive relationships and intensified adolescent engagement, may improve HCT processes and outcomes.